Teaching the Last Backpack Generation : a Mobile Technology Handbook for Secondary Educators. - Walker, Zachary (SAGE Publications, 2015)
Let mobile devices transform teaching and learning Don't just know how to use mobile technology. Know how to use it to transform learning. This refreshingly easy-to-use workbook shows educators how to make mobile devices a natural part of their classrooms by optimizing technology, no matter what the content. Discover: practical mobile device management skills such as how to project and use devices as a whiteboard and tools to capture student responses. fun strategies students will love such as teaching vocabulary using text speak and slang or using a digital assistant (like Siri) instead of wr.